Single-cell RNA sequencing highlights a significant retinal Müller glial population in dry age-related macular degeneration - Bing Zeng; Chuanhe Zhang; Yifan Liang; Jianguo Huang; Deshuang Li; Ziling Liu; Hongxia Liao; Tedu Yang; Muyun Liu; Chang Zou; Dongcheng Liu; Bo Qin (iScience)
Summary: The main challenge in dissecting the cells and pathways involved in the pathogenesis of age-related macular degeneration (AMD) is the highly heterogeneous and dynamic nature of the retinal microenvironment. This study aimed to describe the comprehensive landscape of the dry AMD (dAMD) model and identify the key cell cluster contributing to dAMD. We identified a subset of Müller cells that express high levels of Sox2, which play crucial roles in homeostasis and neuroprotection in both mouse models of AMD and patients with dAMD. Additionally, the number of Sox2+ Müller cells decreased significantly during the progression of AMD, indicating these cells were damaged and underwent cell death. Interestingly, ferroptosis and apoptosis were identified as contributors to the damage of Sox2+ Müller cells. Our findings are potentially valuable not only for advancing the current understanding of dAMD progression but also for the development of treatment strategies through the protection of Müller cells.